2021
DOI: 10.3389/fbioe.2021.709965
|View full text |Cite
|
Sign up to set email alerts
|

Hofmeister Effect in RT-QuIC Seeding Activity of Chronic Wasting Disease Prions

Abstract: Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) that causes a fatal neurodegenerative disease in cervids. Cases of CWD are rapidly increasing in North America among wild and farmed cervid populations, and potential for zoonotic transmission is not yet determined. Therefore, in order to manage the disease, it is imperative to devise a system that can detect CWD during its early phases to prevent spread to new captive herds through introduction of CWD-affected animals into otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Overall, RAF was the highest for most samples at 10 –2 dilution followed by 10 –3 and then 10 –1 , indicating the presence of inhibitors at 10 –1 . The positive effects of ASR1 and NaI were in line with previous findings that ASR1 selectively captured a diverse range of misfolded proteins, including vCJD prion in human plasma spiked with vCJD brain tissue [ 26 , 27 ] and NaI enhanced seeding activity of brain and fecal samples [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, RAF was the highest for most samples at 10 –2 dilution followed by 10 –3 and then 10 –1 , indicating the presence of inhibitors at 10 –1 . The positive effects of ASR1 and NaI were in line with previous findings that ASR1 selectively captured a diverse range of misfolded proteins, including vCJD prion in human plasma spiked with vCJD brain tissue [ 26 , 27 ] and NaI enhanced seeding activity of brain and fecal samples [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…Pre-treatment of samples with ASR1 enhanced the detection of prions in human plasma samples [ 27 ]. Besides preanalytical enrichment, Hofmeister anions from weakly hydrating to strongly hydrating could affect prion seeding activity via modifying the ionic environment of RT-QuIC [ 28 , 29 ]. Sodium iodide, a weakly hydrated and solubilizing salt, improved the kinetic separation of prion-seeding in scrapie prion RT-QuIC assays, thereby affecting assay sensitivity and specificity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RT-QuIC assay is extremely sensitive and able to detect sub-femtograms of infectious or misfolded prion proteins, which seed the conversion or aggregation of monomeric prion substrates to form larger amyloid fibrils [ 14 , 15 ]. The kinetics of amyloid fibril formation are affected by the types and concentrations of salts [ 27 ] or solvents [ 28 ] in the assay solutions and also by the assay temperatures and shaking arrangements [ 28 ]. As such, a wide range of assay durations have been used in RT-QuIC for the detection of CWD [ 5 , 6 , 7 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our findings demonstrated the effectiveness of using ROC and AUC analyses for optimizing RT-QuIC assay durations in screening CWD as an alternative to ELISA. As many factors may affect RT-QuIC performance [ 9 , 27 , 28 ], it is expected that the optimal assay duration may vary for different sample matrixes, with different substrates and reagents, and using different fluorometers. In addition, with ROC curves, there are multiple methods to interpret the optimal threshold cut-offs, such as the Youden index and the point closest to the (0,1) method [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been studied in biological systems (e.g., proteins, , enzymes, , biochannels, and lipids , ), but Hofmeister effects have often been ignored in living organisms, although they are generally based on various aqueous salts including numerous anions and cations, which are listed in the Hofmeister series. For anions, ClO 4 – , SCN – , and NO 3 – can act as inhibitors of iodide transport which might affect the function of the thyroid, , ClO 4 – also can affect the release of insulin, and Br – has been applied as a drug to treat epilepsy. , Hofmeister series anions have been reported to affect in vitro aggregation of several amyloidogenic proteins, which are involved in the onset of neurodegenerative disease. Recently, we observed that counteranions in the stimulation solution alter the dynamics of exocytosis that can be explained by immediate Hofmeister effects on lipid bilayers of the cell membrane . Of particular interest, however, is the investigation of the Hofmeister effect in living biological models (e.g., cell, tissue, and animal).…”
mentioning
confidence: 99%